Lichen planus of the esophagus: a case report - Elvira Guarner; Fatimetu Mohamed; David Busquets; Begoña Fuertes Negro; Rosa Ortiz; Berta Oliveras; Carlos Huertas; Carme López (Frontiers in Medicine, 2023)
Esophageal lichen planus (ELP) is an inflammatory disorder that affects the skin, cutaneous appendages and mucous membranes. The esophageal involvement is rare. We present the case of a 70-year-old woman with years of dysphagia and a history of erosive lichen planus involving the vulva, vagina, gingiva, and skin, who was eventually diagnosed with esophageal lichen planus. The patient's condition was refractory and progressed to the development of intraepithelial squamous neoplasia. We reviewed the literature on this condition.